Analysis of Technology Transfer Efficiency and Associated Socio-personal Variables Among the Fishery Extension Personnel in Kerala - J. Charles Jeeva , J. Vasanthakumar andS. Balasubramaniam, (Indian Journal of Extension Education, 2013)
This paper deals with the assessment of technology transfer efficiency and identification of influencing socio-personalcharacteristics among the fisheries extension personnel in Kerala. The results revealed that the overall technology transfer efficiency index was 91.70 with the standard deviation of 8.83. The extent of adoption of the identified activities in thetechnology transfer process was more than 90.00 per cent for almost all the items. The regression analysis revealed thatthree variables viz., time utilization in extension works, communication behaviour and extent of linkage with research and 2 clientele groups had contributed significantly and positively towards the efficiency in technology transfer process. The R value indicated that all the variables taken together served as cause for explaining 81.20 per cent of variation in the efficiency level. The highly significant 'F' value revealed the overall significance of the regression at one percent level of probability. The constraints in the technology transfer process, as perceived by the extension personnel are also discussed in the paper.